Post-chemoradiation volumetric response predicts survival in newly diagnosed glioblastoma treated with radiation, temozolomide, and bevacizumab or placebo. Issue 11 (20th April 2018) - Ellingson, Benjamin M; Abrey, Lauren E; Garcia, Josep; Chinot, Olivier; Wick, Wolfgang; Saran, Frank; Nishikawa, Ryo; Henriksson, Roger; Mason, Warren P; Harris, Robert J; Leu, Kevin; Woodworth, Davis C; et al.
Abstract: Background: In the current study we used contrast-enhanced T1 subtraction maps to test whether early changes in enhancing tumor volume are prognostic for overall survival (OS) in newly diagnosed glioblastoma (GBM) patients treated with chemoradiation with or without bevacizumab (BV). Methods: Seven hundred ninety-eight patients (404 BV and 394 placebo) with newly diagnosed GBM in the AVAglio trial (NCT00943826) had baseline MRI scans available, while 337 BV-treated and 269 placebo-treated patients had >4 MRI scans for response evaluation. The volume of contrast-enhancing tumor was quantified and used for subsequent analyses. Results: A decrease in tumor volume during chemoradiation was associated with a longer OS in the placebo group (hazard ratio [HR] = 1.578, P < 0.0001) but not BV-treated group (HR = 1.135, P = 0.4889). Results showed a higher OS in patients on the placebo arm with a sustained decrease in tumor volume using a post-chemoradiation baseline (HR = 1.692, P = 0.0005), and a trend toward longer OS was seen in BV-treated patients (HR = 1.264, P = 0.0724). Multivariable Cox regression confirmed that sustained response or stable disease was prognostic for OS (HR = 0.7509, P = 0.0127) when accounting for age ( P = 0.0002), KPS ( P = 0.1516), postsurgical tumor volume ( P < 0.0001), O 6 -methylguanine-DNA methyltransferase status ( P < 0.0001), and treatment type ( P = 0.7637) using the post-chemoradiation baseline. Conclusions: The post-chemoradiation timepoint is a better baseline for evaluating efficacy in newly diagnosed GBM. Early progression during the maintenance phase is consequential in predicting OS, supporting the use of progression-free survival rates as a meaningful surrogate for GBM.